Drillbit Taylor [videorecording (DVD)] - Brill, Steven; Wilson, Owen, 1968-; Hartley, Nate; Gentile, Troy (Paramount Home Entertainment, 2008)
Ryan, Wade and Emmit attend their first day of high school and immediately meet up with Filkins, the school bully who comes off like a little Hannibal Lecter. Before they become completely engulfed in Filkins' reign of terror, they seek out some protection by placing an ad in Soldier of fortune magazine. Their best response and the cheapest comes from Drillbit Taylor, a down-on-his-luck soldier of furtune who lives a homeless existence on the beach. He enrolls them in a sort of physical and mental training, steeling them, and possibly himself, for the ultimate clash against the forces keeping them down.